PENGARUH PEKERJA PEREMPUAN AND ISLAMIC HUMAN DEVELOPMENT INDEX TINGKAT KEMISKINAN DI INDONESIA - Ulya Safira; Sri Wahyuni; Azka Rizkina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Penury remains a major challenge in Indonesia's development plans and is influenced by many economic and social factors. To fight poverty well, we need a combined approach that includes helping more people, especially women, find jobs and improving education and health in a way that follows Islamic values. This is shown through the IHDI. More women taking part in the economy should lead to higher family income, and human development that includes spiritual and social values is likely to help with lasting and sustainable happiness. This study aims to look at how women's involvement in work and the Islamic Human Development Index affect poverty in Indonesia, using a quantitative time series approach. The study uses yearly data from 2010 to 2024, which comes from Indonesia's Central Statistics Agency (BPS) as well as different publications and reports that are connected to measuring the IHDI. Multiple linear regression analysis, using the Ordinary Least Squares method, is used to determine how much female workers and the IHDI affect poverty levels in Indonesia. The study shows that when more women work, it makes a big difference in reducing poverty in Indonesia. This means that having more women in jobs helps families earn more money and stay financially stable, which in turn helps cut down poverty. The results also show that the IHDI is linked in a negative and important way to poverty, meaning that when human development is based on Islamic values, it helps create better and more lasting social welfare outcomes.